Teacher-in-role as a problem-posing method for learners in a special needs school in South Africa - Hellemann, Phemelo Cordelia (Rhodes University, Faculty of Humanities, Department of Drama, 2018)
Paulo Freire's problem-posing pedagogy urges for a creative and collaborative educational environment between learners and teachers that encourages critical thinking and engagement. This research explores how special needs pedagogical approaches in South Africa can transform their classroom practices to embrace creative and collaborative teaching methods such as drama. Drama-in-education (D-i-E) is an area where the learner and teacher relationship is characterised by creativity and engagement. This qualitative study considers the uses of drama as a teaching and learning method for learners in the Skills Phase class at Kuyasa Special School, Grahamstown. The research aimed to provide learners with intellectual barriers to learning with access to D-i-E. This was done through a series of practical drama lessons, which broadly aimed to enhance life skills and work environment competencies such as communication, problem-solving and interpersonal relations. The lessons followed a cross- curricular approach that integrated aspects of the Life Orientation (Grade 10-12) curriculum and the Drama (Creative Arts Grade 7-9) curriculum. This practice-led study reflects on how Dorothy Heathcote's teacher-in-role (t-i-r) drama technique was implemented to teach topics and themes extracted and adapted from the Life Orientation learning area. This drama-based pedagogy employs three elements of Freire's problem-posing education model, which are learner-centred, problem-posing and liberated pedagogy. The study discusses how these elements manifested in the lessons conducted, and how this approach benefited and improved the learners' critical thinking skills, self-esteem and confidence. This study therefore provides a broad understanding of the possibilities of a drama-based pedagogy within a South Africa context of learning disability, proposing an alternative pedagogical approach in South African special schools. The findings contribute to the academic literature on D-i-E in South Africa and advocate for the inclusion of learners with learning disabilities within the performing arts education.
Keywords: Special education -- Activity programs -- South Africa; Special education -- South Africa; Drama in education -- South Africa; Drama -- Therapeutic use -- South Africa; Children with mental disabilities -- Life skills guides; Kuyasa School (South Africa)